Critical perspectives on labor unions - Santos, Rita, 1985- (Analyzing the issues., 2020)
Explores a wide range of perspectives and thought on the topic of labor unions, with excerpts from statements made by experts, politicians, advocacy groups, the media, and ordinary people from around the world.